What’s Wrong with this Picture? - Herndon, J. Marvin (Advances in Social Sciences Research Journal, 2022)
A recent publication in Nature unintentionally disclosed major problems in the physical science community, existing for more than four decades that pose potential weaknesses as a basis for future technologies. The science of today, the basis for tomorrow’s technology, could benefit in a major way, simply by asking the question “What’s wrong with this picture?”